Hospitality situations, consumer expertise, and perceptions of wine attributes: three empirical studies. Issue 1 (11th March 2019) - Duhan, Dale F.; Rinaldo, Shannon B.; Velikova, Natalia; Dodd, Tim; Trela, Brent
Abstract : Purpose: Wine choices are not always fully understood by academic researchers or the industry. This paper aims to outline and test a theoretical model proposing that wine consumption may be dependent on differences in consumer expertise, the hospitality situation, characteristics of the wine itself and an interaction of these variables. Design/methodology/approach: Three empirical studies (total sample size = 356) tested these theoretical propositions. Consumers with varying levels of wine knowledge were presented with experimental vignettes showing videos of wine opening and pouring and were asked to pair wines with hospitality situations. Findings: Study 1 found that consumers with low product knowledge were more sensitive to hospitality situations and extrinsic product attributes (closures) than were the experts. Study 2 found that wine hospitality situations fall into three predicted categories, namely, food, friends and formality, although contrary to prediction, the presence of food was the weakest predictors. Study 3 demonstrated the robustness of the three-dimensional structure of wine hospitality situations. Practical implications: These studies provided important practical information because targeting various market segments requires the industry to know what product attributes are favored by different groups of consumers different situations. Originality/value: Previous researchers have discussed the difficulty of measuring consumption situations. By limiting these studies to wine consumption within hospitality situations, the authors learned much about how consumers' characteristics, product attributes and the situations interact to influence not only product assessments but also choices.